New insights into the debates on rural indebtedness in 19th century Deccan - Rao, Parimala V. (2009)
The peasantry in the Deccan suffered from widespread indebtedness during the 19th century, in March 1881, after touring the rural areas of Poona and Ahmadnagar districts, which were still recovering from the devastations caused by famine and the credit crunch followed by the peasant revolt of 1876-79, Mahadev Govind Ranade proposed the establishment of Agricultural-Shetkari banks. The nationalists led by Bal Gangadhar Tilak opposed the proposal. This article explores the debates on peasant indebtedness and the intervention of nationalists on behalf of the moneylenders to oppose even limited measures to assist peasants in the rural economy. - Reproduced.
Keywords: Peasantry